Gospel sonnets: or Spiritual songs ... - Erskine, Ralph (Benson collection of hymnals and hymnology, 1762)
I. The believer's espousals. -- II. The believer's jointure. -- III. The believer's riddle. -- IV. The believer's lodging. -- V. The believer's soliloquy. -- VI. The believer's principles.